The lion, the witch and the wardrobe - Lawrie, Robin; Lewis, C. S., (Clive Staples), 1898-1963. (New York, NY : HarperTrophy, 1995)
Text and cartoon illustrations recount the adventures of four English schoolchildren who find their way through the back of a wardrobe into the magical land of Narnia and assist Aslan, the golden lion, in his triumph over the White Witch, who has cursed the land with eternal winter.
"First published in a Lions edition, an imprint of HarperCollins Publishers Ltd., ... London"--T.p. verso.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
5.9.
5.9
Keywords: Fantasy; Fantastic fiction